A Critical Review of MELD as a Reliable Tool for Transplant Prioritization - Sacleux, Sophie-Caroline; Samuel, Didier (Seminars in Liver Disease, 2019)
In a context of global organ shortage, the Model for End-Stage Liver Disease (MELD) score seems to be a fair prioritization tool, with a paradigm: “sickest first.” Since its introduction in the United States in 2002, it has been rapidly adopted by transplant centers and organ sharing agencies around the world. The MELD score showed its effectiveness with a 12% reduction in waiting list mortality in the United States. Its success is linked to its simplicity, the use of basic variables (serum creatinine, serum bilirubin, and international normalized ratio [INR]), and its ability to predict short-term mortality, particularly on the transplant waiting list. However, this score is not perfect: its variables may have disadvantages for some patients, especially women, with serum creatinine and interlaboratory variability of the INR. The MELD score does not take into account some variables associated with poor short-term prognosis in cirrhotic patients. In addition, it is currently capped at 40, which results in the exclusion of sicker patients who could greatly benefit from transplantation. Finally, the MELD score does not accurately reflect the prognosis of several conditions, requiring a MELD exception system. Some solutions have been suggested such as MELD-Na or MELD uncapping, but it has not yet been fully accepted by all transplant centers.
Keywords: Model for End-Stage Liver Disease; liver transplantation; MELD exception; acute-on-chronic liver failure; prioritization